Power Sector Reforms and Citizen-centered Social Policy in Nigeria - Olufemi, Oladosu (Kashere Journal of Politics and International Relations, 2025)
The Power sector reforms in Nigeria have evolved overtime. It aims to significantly revolutionize the electricity industry concomitant with various economic reform measures like privatization, liberalization, deregulation and regulatory changes. The maximization of social gain is the heartbeat of public policies. The core focus of these reforms is the need to create a loop of technicality, market-driven changes and citizen-centered social policy goals. The Electricity Act 2023 was a watershed in efforts to decentralize ownership, control, management and regulation to the sub-nationals. This was designed to sustainably promote renewable energy integration, and encouraging localized electricity markets. However, encumbrances surrounding political will, haphazard privatization, weak regulatory enforcement, gaps in infrastructural investments, and politicization of development drives continue to thwart progress, affect service provision and cost advantage for many Nigerians. Relying on a descriptive analysis of available secondary information, this study thematically reviews concepts that are related to power reform and social policy. With the use of systems theory, the power sector operates within an organically connected ecosystem where reform policies, operators, and citizen experiences create a continuum of feedback, mutually reinforcing one another. It was noted that effective reforms hinged on adequate political will must therefore institutionalize mechanisms for citizen involvement, autonomy for market actors, transparent tariff-setting and social protection to ensure equitable outcomes. To enhance the social impact of reforms policy, the study recommends strengthening operational independence and adequate regulatory schemes to enforce corporate social responsibilities and obligations of power sector investments to the citizenry.